Морфо-экологическая характеристика уклеи некоторых водоемов Украины - Мовчан, Ю.В.; Рогинская, И.М. (Вестник зоологии, 1983)
A detailed study in morphology characters of the bleak, Alburnus alburnus (L), from four water bodies of the Ukraine, where it is presented by nominate subspecies. Size-age and geographic variations are described, clinal intergradation of some characters is pointed out. New data on feeding, fecundity, fatness and growth rate are communicated.